2018
DOI: 10.1155/2018/8641893
|View full text |Cite
|
Sign up to set email alerts
|

Combining Acute Kidney Injury with Gastrointestinal Pathology: A Clue to Acute Oxalate Nephropathy

Abstract: Acute oxalate nephropathy (AON) is an increasingly recognized cause of acute kidney injury (AKI). Herein, we present two cases of biopsy-proven acute oxalate nephropathy in patients with gastrointestinal malabsorption, coincidentally both stemming from cholangiocarcinoma. The first is a 73-year-old male who presented with syncope and was found to have severe, oliguric AKI in the setting of newly diagnosed, nonresectable cholangiocarcinoma. The second is a 64-year-old man with remote resection of cholangiocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…During the acute supersaturation phase, CaOx complexes are the most common type of kidney stone, which was initially referred to as type 2 crystalline nephropathy ( Mulay et al, 2018 ). Under this condition, tubular injury is associated with crystals and/or Tamm–Horsfall protein (THP) complexes, apoptotic and inflammatory responses consistent with acute kidney injury (AKI), in addition to the risk for recurrence and/or chronic kidney disease (CKD) progression ( Lorenz et al, 2014 ; Pfau and Knauf, 2016 ; Fox et al, 2018 ; Mulay et al, 2018 ; Efe et al, 2019 ). However, clinical evidence and experimental models of ischemia-reperfusion have revealed that frequently, the recovery of renal function after AKI is incomplete and accompanied by proteinuria, tubular injury and glomerular filtration rate (GFR) decline, leading to end-stage renal disease (ESRD) ( Hingorani et al, 2009 ; Basile et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the acute supersaturation phase, CaOx complexes are the most common type of kidney stone, which was initially referred to as type 2 crystalline nephropathy ( Mulay et al, 2018 ). Under this condition, tubular injury is associated with crystals and/or Tamm–Horsfall protein (THP) complexes, apoptotic and inflammatory responses consistent with acute kidney injury (AKI), in addition to the risk for recurrence and/or chronic kidney disease (CKD) progression ( Lorenz et al, 2014 ; Pfau and Knauf, 2016 ; Fox et al, 2018 ; Mulay et al, 2018 ; Efe et al, 2019 ). However, clinical evidence and experimental models of ischemia-reperfusion have revealed that frequently, the recovery of renal function after AKI is incomplete and accompanied by proteinuria, tubular injury and glomerular filtration rate (GFR) decline, leading to end-stage renal disease (ESRD) ( Hingorani et al, 2009 ; Basile et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro studies showed that prostaglandins may decrease the adhesion ability of calcium oxalate to renal epithelial cells ( 25 , 26 ). As NSAIDs downregulate prostaglandin production ( 27 ), it is feasible to speculate that NSAID use is predisposed to a greater likelihood of adhesion of oxalate crystals to the tubular epithelium. In this regard, we hypothesize that factors, which either decrease urinary flow in renal tubules or increase the adhesion ability of oxalate crystals to the epithelium, contribute convergently to the development of acute oxalate nephropathy when superimposed on hyperoxaluria in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins may decrease calcium oxalate adhesion to renal epithelial cells [ 58 , 59 ]. Nonsteroidal anti-inflammatory drugs downregulate prostaglandin production; therefore, it is feasible that Nonsteroidal anti-inflammatory drugs predispose to a greater likelihood of stone formation [ 60 ]. Furthermore, proteins such as osteopontin are also constantly embedded in the interstitium in the CaOx formation progress, which binds to CD44, a membrane-bound glycoprotein on proximal renal tubular epithelial cells.…”
Section: Oxalate Nephropathy and Kidney Injurymentioning
confidence: 99%